The relationships between reading fluency and different measures of holistic word processing - Ventura, Paulo (2022)
Recently, paradigms in the face recognition literature have been adopted to reveal holistic processing in word recognition. It is unknown, however, whether different measures of holistic word processing share similar underlying mechanisms, and whether fluent word reading relies on holistic word processing. We measured holistic processing effects in three paradigms (composite, configural sensitivity, part–whole) as well as in reading fluency (3DM task: reading aloud high- and low-frequency words and pseudowords). Bin scores were used to combine accuracy and response time variables in the quest for a more comprehensive, reliable, and valid measure of holistic processing. Weak correlations were found between the different holistic processing measures, with only a significant correlation between the configural sensitivity effect and part–whole effect (r = .32) and a trend of a positive correlation between the word composite effect and configural sensitivity effect (r = .21). Of the three holistic processing measures, only one (part–whole effect) correlated with a lexical access measure of 3DM (r = .23). We also performed a principal component analysis (PCA) of performance in the three lists of 3DM, with the second most probably reflecting lexical access processes. There was a tendency for a positive correlation between part–whole bin measure and Component 2 of PCA. We also found a positive correlation between composite aligned in accuracy and Component 2 of PCA. Our results show that different measures of holistic word processing reflect predominantly different mechanisms, and that differences among normal readers in word reading do not seem to depend highly on holistic processing.